Instagram Promotion in Facilitating Library Long-Distance Service Utilization - Alfiah, Siti; Irfaniah, Hikmah (Librarianship in Muslim Societies, 2024)
Trisakti University Library provides Long-Distance Services (LDS) that users can utilize during the pandemic. To increase the use of library services, the intensity of promotion through Instagram needs to be increased as well. This study aims to determine the effect of library promotion through Instagram on the utilization of LDS at Trisakti University Library. This type of research is associative research with a quantitative approach. The research sample was 93 respondents who are students and Instagram followers. They obtained from a total population of 1,323 @usakti_library followers by using the Slovin formula with an accidental sampling technique. Data analysis used a simple linear regression test to test the effect of Variable X and Y. The results showed that there was a significant effect between library promotion through Instagram (X) and Remote Service Utilization (Y), with a significance value of 0‚000 < 0,05 (5%). This is also strengthened by a strong correlation level of 0‚694 on a scale of 0.60 – 0.799. The result of the R Square value is 0‚482. It proves that library promotion influences 48,2% of LDS. The results of this study confirm the uses and effects theory stating that the use of mass media and media content will cause certain effect. In this study, the effect is the increased utilization of LDS. It is hoped that this research can help the library in increasing promotional activities through Instagram and its attention in processing library services. This research is expected to help the library to increase promotional activities through Instagram and to improve service quality.